Analisis Semiotika Charles Sanders Peirce Pada Iklan Telkomsel Semangat Indonesia - Syuhada, Farhan; Thariq, Muhammad (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
An attractive advertising concept that connects products with nuances of beauty, progress, natural wealth, cooperation or mutual cooperation and differences in Indonesia is displayed by Telkomsel. With the theme or title "Indonesian spirit", as of March 22, 2024, Telkomsel's advertisement had been seen and viewed 17.5 million times. This research aims to find out the meaning of the message contained in each advertising scene and also to find out the meaning of the message and information that Telkomsel wants to convey to its target market through its advertisement, namely the Spirit of Indonesia. This type of research is qualitative using the semiotic analysis method by Charles Sanders Peirce which uses the triangle theory of meaning or triadic theory which divides analytical data into three elements, namely sign, object and interpretant. From the results of this research, it can be seen that the meaning in each scene of Telkomsel's Indonesian spirit advertisement is that Indonesia has its own spirit, namely the spirit of never backing down, overcoming various obstacles, working together, mutual cooperation, and helping each other, united and not looking at differences. Telkomsel, through its Indonesian spirit advertisement, also conveys messages or information to its marketing targets, namely that Telkomsel will continue to innovate, create togetherness, open up space for the Indonesian people, care more about the Indonesian people and nation, help the movement of the Indonesian economy and prioritize the progress of the Indonesian nation.